The Influence of Moral Culture Dimensions on the Quality of Public Services at PT. PLN (Persero) Main Unit for South Sulawesi Region - Nur Asmi Rahim; Samsul Rizal; Irwan Abdullah (Pustaka Digital Indonesia, 2024)
This research is a type of quantitative research with the aim of finding out the influence of the dimensions of moral culture on the quality of public services at PT PLN (Persero) Main Unit for the South Sulawesi Region. The type of data used in this research is quantitative obtained from distributed questionnaires and is related to the problem being studied. In research, the data sources used in data collection include primary and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using the SPSS version 25 calculation application, the statistical results of the trustworthiness core value variable test obtained a t value of 10.781, competent core value obtained a t value of 19.639, harmonious core value obtained a t value of 5.297, loyal core value obtained a t value of 5.297. 23.374, the adaptive core value obtained a calculated t value of 7.163, the collaborative core value obtained a calculated t value of 4.601 from the t table value of 0.2352 and obtained a sig value of 0.000 from a significant value of 0.05